Shi'ism : a religion of protest - Dabashi, Hamid, 1951- (Belknap Press of Harvard University Press, 2011)
"For a Western world anxious to understand Islam and, in particular, Shi'ism, this book arrives with urgently needed information and critical analysis. Hamid Dabashi exposes the soul of Shi'ism as a religion of protest - successful only when in a warring position, and losing its legitimacy when in power